Wearable and implantable medical devices : applications and challenges - Dey, Nilanjan, 1984-; Ashour, Amira, 1975-; Fong, Simon; Bhatt, Chintan M., 1988- (Academic Press, 2020)
"Wearable and Implantable Medical Devices: Applications and Challenges, Fourth Edition highlights the new aspects of wearable and implanted sensors technology in the healthcare sector and monitoring systems. The book's contributions include several interdisciplinary domains, such as wearable sensors, implanted sensors devices, Internet-of-Things (IoT), security, real-time medical healthcare monitoring, WIBSN design and data management, encryption, and decision-support systems. Contributions emphasize several topics, including real-world applications and the design and implementation of wearable devices. This book demonstrates that this new field has a brilliant future in applied healthcare research and in healthcare monitoring systems."--ScienceDirect
4.3.2 AdaptableSDA: hop-by-hop integrity
Keywords: Medical instruments and apparatus.; elektronické knihy; electronic books